Positive pressure ventilation improves exercise performance and attenuates the fall of postexercise inspiratory muscular strength in rower athlete - Gonçalves, T. R.; Soares, P. P. D. S. (The Journal of Strength and Conditioning Research, 2021)
Positive pressure ventilation (PPV) can increase exercise performance in cyclists, but its effects are unclear in other exercise modes, especially those using large muscle mass. The aim of this study was to compare the exercise performance and postexercise inspiratory muscles' strength with and without PPV (NO-PPV) during rowing. Nine male rowers (19 ± 1 year) participated in 3 experimental days (M1, M2, and M3) separated by 1 week. In M1, rowers performed a 2,000-m test (2k) on a rowing ergometer to obtain average power (W2k). In M2 and M3, the rowers performed 4 minutes' workouts at 55, 65, 75, and 85% W2k, respectively, separated by 1 minute of recovery, with PPV and NO-PPV application in randomized order. Blood lactate (La) was measured during intervals. After submaximal exercises, with 10 minutes of "cool down," the rowers performed a maximal performance test of 4 minutes (4-minute all-out rowing). Traveled distance was computed and correlated with maximal inspiratory pressure (MIP) changes from pretest to posttest (Delta). Positive pressure ventilation application increased the traveled distance in relation to NO-PPV exercise (1,210.7 ± 45.5 vs. 1,199.8 ± 43.4 m, p = 0.05). The DeltaMIP (cmH2O) was lower in PPV as compared to NO-PPV exercise (-19.1 ± 10.2 vs. -26.3 ± 7.9 cmH2O, p = 0.05). The [La] showed no significant difference between PPV and NO-PPV exercises (p > 0.05). Therefore, the PPV during whole-body rowing exercise improved the exercise performance and attenuated the inspiratory postexercise fatigue. These findings suggest that inspiratory muscles' strength plays a role during high-intensity exercise with large muscle mass.